2023
DOI: 10.2106/jbjs.22.01124
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Glenoid Articular Cartilage Varies Across Acute Instability, Chronic Instability, and Osteoarthritis

Abstract: Background: Shoulder instability is a common pathology associated with an elevated risk of osteoarthritis (OA). Little is known about gene expression in the cartilage of the glenohumeral joint after dislocation events, particularly as it relates to the risk of posttraumatic OA. This study tested the hypothesis that gene expression in glenoid cartilage varies among acute instability (<3 dislocations), chronic instability ( ‡3 dislocations), and OA.Methods: Articular cartilage was collected from the anteroinferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For example, a higher level of PRKAR2B was observed in the cartilage of patients with osteoarthritis compared with those with acute or chronic instability. 32 PRKAR2B has also been linked to the diagnosis/prognosis of type 2 diabetes, 33 chronic obstructive pulmonary disease, 34 and hypertension. 35 …”
Section: Discussionmentioning
confidence: 99%
“…For example, a higher level of PRKAR2B was observed in the cartilage of patients with osteoarthritis compared with those with acute or chronic instability. 32 PRKAR2B has also been linked to the diagnosis/prognosis of type 2 diabetes, 33 chronic obstructive pulmonary disease, 34 and hypertension. 35 …”
Section: Discussionmentioning
confidence: 99%
“…They found that POSTN had a higher expression in articular cartilage of shoulders with acute instability compared with shoulders with osteoarthritis. 1 Interestingly, tandem mass spectrometry identified POSTN as a significant protein of interest in the glenohumeral joint of patients with anterior shoulder instability. This begs the question of what is similar about the injury-specific factors between ACL tears and anterior shoulder dislocations.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this, a team from St Louis (Missouri, USA) collected articular cartilage from the anteroinferior glenoid of 17 consenting patients who were undergoing shoulder stabilization surgery, and 16 undergoing total shoulder arthroplasty. 3 Digital quantitative polymerase chain reaction was used to assess the relative expression of a panel of 57 candidate genes. These were selected as 36 from OA risk allele studies, and 21 from differential expression studies which compared OA to acute and chronic instability.…”
Section: Gene Expression In Glenoid Articular Cartilage Varies In Acu...mentioning
confidence: 99%